2020
DOI: 10.1186/s13054-020-03148-2
|View full text |Cite
|
Sign up to set email alerts
|

Nebulised heparin as a treatment for COVID-19: scientific rationale and a call for randomised evidence

Abstract: Nebulised unfractionated heparin (UFH) has a strong scientific and biological rationale and warrants urgent investigation of its therapeutic potential, for COVID-19-induced acute respiratory distress syndrome (ARDS). COVID-19 ARDS displays the typical features of diffuse alveolar damage with extensive pulmonary coagulation activation resulting in fibrin deposition in the microvasculature and formation of hyaline membranes in the air sacs. Patients infected with SARS-CoV-2 who manifest severe disease have high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 119 publications
(140 reference statements)
1
100
0
2
Order By: Relevance
“…In the United Kingdom, Brazil and Australia, in addition to systemic heparin use, the novel approach of delivering UFH via nebulisation directly to lungs of COVID‐19 patients is undergoing evaluation in a clinical trial by the ACCORD clinical trials platform (https://accord-trial.org/)) (van Haren et al, 2020). This is to determine if there is a benefit from the additional known anti‐inflammatory activity of heparin and to provide high local anti‐coagulant effects on the alveolar region of patients with severe COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom, Brazil and Australia, in addition to systemic heparin use, the novel approach of delivering UFH via nebulisation directly to lungs of COVID‐19 patients is undergoing evaluation in a clinical trial by the ACCORD clinical trials platform (https://accord-trial.org/)) (van Haren et al, 2020). This is to determine if there is a benefit from the additional known anti‐inflammatory activity of heparin and to provide high local anti‐coagulant effects on the alveolar region of patients with severe COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Independent from the systemic use of heparin in COVID‐19 patients, nebulised heparin has been proposed as a unique and potentially effective treatment for different stages of COVID‐19 disease (van Haren et al, 2020). In the United Kingdom, a clinical trial evaluating the effectiveness of nebulised UFH in hospitalised COVID‐19 patients is currently underway (https://accord-trial.org).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary coagulopathy is once again receiving attention because pulmonary thrombosis is frequently seen in patients with COVID-19 pneumonia, 7 , 8 causing increased dead space and severe hypoxaemia. The promising findings of the CHARLI study 3 underline the importance of considering studies of nebulised heparin in patients with COVID-19 pneumonia, 9 and some studies have already been registered on ClinicalTrials.gov ( NCT04397510 , NCT04530578 ). The CHARLI study investigators discuss the need for future studies in more homogeneous populations and we could not agree more; the surges of COVID-19 pneumonia in many countries should trigger the scientific community to test nebulised heparin in these large, uniform populations.…”
mentioning
confidence: 99%
“…showed that anticoagulation therapy using heparin, is presumably associated with a better prognosis in patients infected with COVID-19 ( 133 ). In addition, due to some critical features of unfractionated heparin (UFH), also called nebulized heparin, including anti-coagulant, anti-inflammatory and mucolytic effects, UFH may be a potentially effective treatment for COVID-19 ( 134 ).…”
Section: Immune-based Approachesmentioning
confidence: 99%